Acetylation enhances TET2 function in protecting against abnormal DNA methylation during oxidative stress - Zhang, Yang W. (Mol Cell, 2017)
TET proteins, by converting 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC), are hypothesized, but not directly shown, to protect promoter CpG islands (CGIs) against abnormal DNA methylation (DNAm) in cancer. We define such a protective role linked to DNA damage from oxidative stress (OS) known to induce this abnormality. TET2 removes aberrant DNAm during OS through interacting with DNA methyltransferases (DNMTs) in a “Yin-Yang” complex targeted to chromatin and enhanced by p300 mediated TET2 acetylation. Abnormal gains of DNAm and 5hmC occur simultaneously in OS and knocking down TET2 dynamically alters this balance by enhancing 5mC and reducing 5hmC. TET2 reduction results in hypermethylation of promoter CGIs and enhancers in loci largely overlapping with those induced by OS. Thus, TET2 indeed may protect against abnormal, cancer DNAm in a manner linked to DNA damage.